Diagnostic Laparoscopy Reduces the Rate of Negative Laparotomy in Trauma Patients - Bar, Debashish; Khan, Masrur Akbar; Shashi, Sanjana Sharmin; Rahman, AZM Mahfuzur; Alam, ABM Khurshid; Bhuiyan, Masflque Ahmed; Zim, Hasnat Zaman; Hossain, AZM Mostaque (Journal of Surgical Sciences, 2020)
Background: The last century has witnessed immense evolvement of management of patients with abdominal trauma. Moreover the recent trend has shifted to selective operative management rather than exploratory laparotomy in trauma patients with suspected intraabdominal injuries and is considered more rational as well. Diagnostic laparoscopy is highly sensitive in detecting intra-abdominal injury with subsequent reduction in the rate of negative laparotomy and procedure related morbidity. Objective: The study was carried out to find the role of diagnostic laparoscopy in abdominal trauma. Methods: An observational study was carried out in the casualty block of Dhaka Medical College Hospital from 1st June 2015 to 30th March 2016. A total of 50 successive patients were assigned in this study. All of them were admitted with abdominal trauma and underwent diagnostic laparoscopy during the period of 10 months. The study was designed to find out whether laparoscopy can help in identifying intra-abdominal injuries with consequent avoidance of unnecessary operative explorations. Results: Intra-abdominal injuries other than GIT perforation were diagnosed by laparoscopy with 100% accuracy but in case of bowel injury the diagnostic accuracy was 80%. Conclusion: Diagnostic laparoscopy is the procedure of choice in doubtful intra-abdominal injuries with impressive accuracy except for bowel injury. Subsequently it reduced the need for negative laparotomies with their procedure related adverse effects. Journal of Surgical Sciences (2018) Vol. 22 (1): 47-51